Pregnancy outcomes in women with sickle cell disease at a tertiary hospital in Nigeria: a five-year retrospective study (2024)
Background: Sickle cell disease (SCD) in pregnancy constitutes a high-risk pregnancy, associated with increased risk of adverse outcomes. Objective: To describe the outcome of pregnancy in SCD women managed at the University College Hospital, Ibadan, Nigeria. Materials and Methods: A retrospective review of the health records of sixty-three SCD pregnant women managed between January 1, 2016, and December 31, 2020. The information extracted included sociodemographic and obstetric characteristics, clinical presentations, mode of delivery, maternal and fetal outcomes. The data was analyzed using the IBM Statistical SPSS Statistics for Windows, version 23.0. The test of association was done using Chi-square and level of significance was p<0.05. Results: Prevalence of SCD in pregnant women was 0.65%. Mean age was 28.8±4.1years, 63.5% were haemoglobin SS while 36.5% were haemoglobin SC. Most of the women had tertiary education (61.8%) and booked for antenatal care (ANC) (60%). About 72.4% delivered at term while 46.1% had caesarean delivery. Most common complication was anaemia (79.4%) while vaso-occlusive crisis was the most common type of crisis (55.6%). Most of the women (92.5%) had live-birth with 15.2% of neonates requiring Neonatal Intensive Care Unit (NICU) admission. Maternal death rate was 6.3%. Good maternal and fetal outcomes occurred in 71.4% and 61.9% of participants respectively. Good maternal outcome was significantly associated with tertiary education(p=0.01). Good fetal outcome was associated with tertiary level of education(p=0.04) and multigravida status(p=0.03). Conclusion: SCD pregnant women have good fetal-maternal outcomes, however not receiving ANC and lower level of education were associated with poor pregnancy outcomes. Health education, access to ANC, prompt diagnosis, treatment of complications and multi-disciplinary team management will improve the pregnancy outcomes.